2020
DOI: 10.1519/jsc.0000000000002525
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Effects of Plyometric Training Applied Before or After Regular Soccer Training on Measures of Physical Fitness in Young Players

Abstract: To compare the effects of short-term (i.e., 7 week) plyometric training applied before (PJT-B) or after (PJT-A) soccer practice on components of physical fitness in young soccer players, a single-blind randomized controlled trial was conducted. Post-pubertal boys aged 17.0±0.5 years were allocated to three groups: PJT-B (n=12), PJT-A (n=14), and control (CON; n=12). The outcome measures included tests to evaluate 20-m speed, standing long jump [SLJ], squat jump [SJ], countermovement jump [CMJ], and drop jump [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…In this study, the PJT program included unilateral (Ramirez-Campillo et al, 2015a ), bilateral (Ramirez-Campillo et al, 2015a ), cyclical (Makaruk et al, 2014 ), acyclical (Komi, 2000 ), vertical (Ramirez-Campillo et al, 2015b ), horizontal (Ramirez-Campillo et al, 2015b ), and turn jumps (Hewett et al, 2005 ), in addition to fast and slow SSC muscle contractions (Bobbert, 1990 ), with a strong emphasis on landing technique and shock absorption, using both soft and medium-hard training surfaces (Ramirez-Campillo et al, 2013 ; Kibele et al, 2014 ; Granacher et al, 2015 ). In addition, the PJT was immediately performed after the warm-up program (Ramirez-Campillo et al, 2018c ), participants used individualized box heights (i.e., 5–35 cm) during DJs (Ramirez-Campillo et al, 2018b ), the order of drills was randomized during each week to provide variation to training and to avoid monotony (Ramirez-Campillo et al, 2018c ), and the volume of training was increased progressively (Ramirez-Campillo et al, 2015c ), with a high investigator to participant ratio of 1:5 realized during all PJT sessions (Ramirez-Campillo et al, 2016b ), using an adequate rest between sets (Ramirez-Campillo et al, 2014a ) and repetitions (Ramirez-Campillo et al, 2014b ). Moreover, all PJT sessions were conducted in the specific training surfaces were players usually trained and compete (i.e., grass, land-dirt).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the PJT program included unilateral (Ramirez-Campillo et al, 2015a ), bilateral (Ramirez-Campillo et al, 2015a ), cyclical (Makaruk et al, 2014 ), acyclical (Komi, 2000 ), vertical (Ramirez-Campillo et al, 2015b ), horizontal (Ramirez-Campillo et al, 2015b ), and turn jumps (Hewett et al, 2005 ), in addition to fast and slow SSC muscle contractions (Bobbert, 1990 ), with a strong emphasis on landing technique and shock absorption, using both soft and medium-hard training surfaces (Ramirez-Campillo et al, 2013 ; Kibele et al, 2014 ; Granacher et al, 2015 ). In addition, the PJT was immediately performed after the warm-up program (Ramirez-Campillo et al, 2018c ), participants used individualized box heights (i.e., 5–35 cm) during DJs (Ramirez-Campillo et al, 2018b ), the order of drills was randomized during each week to provide variation to training and to avoid monotony (Ramirez-Campillo et al, 2018c ), and the volume of training was increased progressively (Ramirez-Campillo et al, 2015c ), with a high investigator to participant ratio of 1:5 realized during all PJT sessions (Ramirez-Campillo et al, 2016b ), using an adequate rest between sets (Ramirez-Campillo et al, 2014a ) and repetitions (Ramirez-Campillo et al, 2014b ). Moreover, all PJT sessions were conducted in the specific training surfaces were players usually trained and compete (i.e., grass, land-dirt).…”
Section: Discussionmentioning
confidence: 99%
“…The design of the PJT intervention was based on the players' previous training records and research results (Ramirez-Campillo et al, 2015a , 2018a ) in order to include unilateral, bilateral, cyclical (i.e., repeated), acyclical (i.e., non-repeated), vertical, horizontal, and turn jumps, in addition to fast (< 250-ms of foot-ground contact-time) and slow (≥250-ms of foot-ground contact-time) stretch-shortening cycle (SSC) muscle contractions, with a strong emphasis on landing technique and shock absorption, using both soft and medium-hard training surfaces (Ramirez-Campillo et al, 2013 ; Kibele et al, 2014 ; Granacher et al, 2015 ). The PJT was not added to the regular soccer training but was immediately performed after the warm-up program (Ramirez-Campillo et al, 2018c ) in replacement of some low-intensity technical-tactical soccer drills. In this context, the PJT was performed within the regular 120-min soccer training period, once (PJT-1) or twice (PJT-2) per week during the 8 weeks intervention period.…”
Section: Methodsmentioning
confidence: 99%
“…The plyometric drop jump training groups replaced some technical drills (i.e., ball control, ball pass, ball conduction and dribbling, ball kicking, ball heading exercises) with plyometric drop jump drills within the usual 90-minute practice twice per week (Tuesday and Thursday) for 7 weeks. All plyometric drop jump training sessions lasted ~21 minutes and were performed just after the warm-up to ensure that the players were in a rested state and gained optimal benefits (38). Plyometric drop jump drills included two sets of 10 repetitions of bounce drop jumps from 20, 40, and 60 cm (i.e., 60 contacts) performed on a grass soccer field, as in previous studies (37,40,44), where very similar (37) or identical (40,44) interventions were demonstrated to be highly effective and safe in youth male soccer players.…”
Section: Training Programmentioning
confidence: 99%
“…Plyometric jump training (PJT) is an effective means of physical conditioning to leverage the stretch-shortening cycle (SSC), promoting improvements in skill-related measures of athletic performance, as well as in health and resistance to injury (23). To implement safe and effective PJT programs, several key methodological characteristics should be considered (35), such as variability of drills (15), overload principle (46), intensity of jumps (37), order of drill execution in the training session (38), amongst other factors. In addition to PJT programming configuration, the characteristics of the training participants should also be considered to optimise adaptive responses, especially the biological maturity status among young populations (32).…”
Section: Introductionmentioning
confidence: 99%
“…Plyometric jump training was immediately performed after the warm-up program (26). The three PJT programs replaced two aerobic training sessions per week, which amounted to <6% of the total training load.…”
Section: Training Programmentioning
confidence: 99%